2020
DOI: 10.3390/ijerph17238909
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Influence of Social Leisure Activities on the Progression to the Stage of Frailty in Korean Seniors

Abstract: In this study, we performed a logistic regression analysis according to the frequency of participation in social leisure activities (education, clubs, social groups, volunteer activities, religious activities, and senior citizens’ welfare center use) by men and women aged ≥ 65 years. We investigated the frequency of participation in social leisure activities and their association with the level of frailty (health vs. pre-frailty, health vs. frailty, pre-frailty vs. frailty). This study included 10,297 older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Based on a 2-year cohort, the results from the study of Ye et al showed that social participation was associated with a higher prefrail improvement ( 29 ). Kim et al conducted a cross-sectional study to investigate the frequency of social activity participation and its association with the different levels of frailty ( 27 ). They found that social activities such as leisure and club activities at a frequency of once a week were associated with frailty prevention ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a 2-year cohort, the results from the study of Ye et al showed that social participation was associated with a higher prefrail improvement ( 29 ). Kim et al conducted a cross-sectional study to investigate the frequency of social activity participation and its association with the different levels of frailty ( 27 ). They found that social activities such as leisure and club activities at a frequency of once a week were associated with frailty prevention ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al conducted a cross-sectional study to investigate the frequency of social activity participation and its association with the different levels of frailty ( 27 ). They found that social activities such as leisure and club activities at a frequency of once a week were associated with frailty prevention ( 27 ). The results of this study were in agreement with these previous findings, despite the differences in the setting population, the frailty index domains, and details in the social and intellectual activities included between this study and the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although evidence has not demonstrated the existence of social frailty, strengthening social networks can reduce levels of the disease by improving independence, maintaining a healthier diet, more frequent physical activity, and curbing excessive consumption of alcohol or tobacco [62]. Specific social leisure activities have been evaluated (social clubs and programs, volunteer activities, religious activities, education programs, visit art exhibitions, theater, or cinema) and demonstrated their effect on the relationship between the frequency of the activities and the reduction in the progression of frailty [63,64].…”
Section: Evidence-based Recommendationsmentioning
confidence: 99%
“…Frailty refers to a complex condition that is characterized by the decreased physiological function of multiple organs and systems, and this disease could increase the susceptibility of patients to stressors ( 1 ). Frailty categorizes individuals into three categories: non-frail individuals, pre-frail individuals and frail individuals ( 2 ). Frailty is a dynamic process and patients can shift between different frailty states ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%